Morfofisiologia de gramas ornamentais e esportivas : aspectos anatômicos, morfológicos e de manejo - Silva, Cleusa Maria Kojoroski e (2008)
The goal of this work was to evaluate the morphological development of carpetgrass or São Carlos (Axonopus affinis), Tifton 419 (Cynodon dactylon x C. transvaalensis) and emerald (Zoysia sp.) grasses in response to two levels of soil compactness measured based on relative density (natural condition, DR=0.67; compact condition, DR=0.85). On greenhouse condition, Tifton 419 had the largest stolon (83.3 cm), height (23.6 cm) and number of leaves (12-24.cm-1 of stolon); the leaves measured 6.7 cm x 1.9 mm (fine texture). Carpetgrass stolons reached 58.3 cm, were thicker (2.5 cm) and produced 2-3 leaves.cm of stolon-1, which were the largest, 10.9 cm x 12.3 mm (coarse texture). Emerald had the lowest height (10 cm), stolon length (45 cm), leaf number (7.cm of stolon-1) which measured 6.2 cm x 3.7 mm (medium texture). The dry matter (DM) accumulation (mg.planta-1) reached 12,100 (carpet-grass), 8,700 (Tifton 419) and 3,500 (emerald) and the root:shoot relation was 0.33, 0.15, and 0.19, respectively. On field condition the fresh (FM) and DM production was evaluated through cuttings. Only carpetgrass was affected by soil compactness in relation to FM and neutral detergent fiber (N1= 1,324 g FM.m-2 and NDF= 71.5%; N2= 1,786 g FM.m-2 and NDF= 65.8%). During the 142 days, carpetgrass was cut six times and the others four times. In natural condition (DR=0,67) the total productions of carpetgrass (409 g DM.m-2) and Tifton 419 (377 g DM.m-2) were bigger than emerald (180 g DM.m-2) in natural soil condition. The Tifton 419 showed greater density of FM (3,971 g.cm-3) compared to carpetgrass (2,063 g.cm-3) and emerald (1,498 g.cm3). Tifton 419 showed the smallest elasticity (GE= 47.7 seconds), carpetgrass, 27.7 seconds and emerald, 30.3 seconds. Because of the greater amount of sclerenchyma, lignification of vascular bundles, and parenchyma cell compactness, Tifton 419 (NDF= 74.2%) and emerald (NDF= 74.8%) had greater rigidity than carpetgrass (NDF= 68.7%)